16.55% efficiency ternary organic solar cells enabled by incorporating a small molecular donor. Issue 45 (4th November 2019) - Yan, Tingting; Ge, Jinfeng; Lei, Tao; Zhang, Wenxia; Song, Wei; Fanady, Billy; Zhang, Danli; Chen, Sanhui; Peng, Ruixiang; Ge, Ziyi
Abstract : A 16.55% high efficiency organic solar cell was achieved by employing a PM6:SM1:Y6 system with an effective and simple ternary strategy. Abstract : The introduction of a third component into the binary system to construct a ternary architecture is widely applied to improve the power conversion efficiency (PCE) of organic solar cells (OSCs). Herein, a small molecule donor, SM1, was introduced into the PM6:Y6 binary system where a high PCE of up to 16.55% was achieved after the addition of 15 wt% of SM1 in the donors with an open-circuit voltage ( V oc ) of 0.831 V, a short-circuit current density ( J sc ) of 25.7 mA cm −2, and a fill factor (FF) of 77.5%, which was much higher than that of the PM6:Y6 binary systems (15.75%), presenting a V oc of 0.845 V, a J sc of 25.3 mA cm −2, and a FF of 73.7%. The introduction of SM1 improved the charge extraction, exciton dissociation, and blend of the morphology while effectively reducing bimolecular recombination. As a result, the J sc and FF of the ternary devices greatly improved. This study presents an effective method to improve the PCE by adopting a ternary strategy, while at the same time, promoting a simple fabrication technology.